Taguchi-Based Optimization of TIG Welding for Joining Low-Carbon Steel (ST37) and Stainless Steel (SUS 304) - Khoirudin; Karyadi, Karyadi; Kusnadi, Akhmad; Amir, Amir; Abdulah, Amri; Hananto, Agus; Taufik Ulhakim, Muhamad (Jurnal Teknik Mesin Mechanical Xplore, 2024)
This study investigates the optimization of tungsten inert gas (TIG) welding parameters for joining dissimilar metals, specifically ST37 low-carbon steel and SUS 304 stainless steel, using the Taguchi L9 experimental design. The welding parameters evaluated include welding current (45-65 A), tungsten electrode diameter (1.6-2.4 mm), and shielding gas flow rate (12-18 LPM). The aim is to enhance joint integrity and mechanical properties by systematically analyzing the influence of these parameters on hardness and tensile load (TS loads). Hardness testing revealed that the weld zone exhibited the highest hardness, followed by the heat-affected zone and base metal. Tensile testing showed that the highest TS loads of 341 kgf were achieved at 45 A, 1.6 mm electrode diameter, and 12 LPM gas flow rate. Signal-to-noise ratio analysis and analysis of variance (ANOVA) indicated that welding current had the most significant influence on hardness and TS loads, with contributions of 39% and 41.27%, respectively, followed by electrode diameter (17% and 36.42%). In comparison, the gas flow rate had the least impact (45% and 22.31%). However, ANOVA results showed that none of the factors exhibited statistical significance (P > 0.05). The findings contribute to the field of welding engineering by providing optimized TIG welding parameters for ST37-SUS 304 joints, enhancing their reliability in various industrial applications such as automotive manufacturing, oil and gas, and power generation, where durable and corrosion-resistant welds are crucial.